Murine 12(R)-lipoxygenase: functional expression, genomic structure and chromosomal localization - Krieg, Peter; Marks, Friedrich; Fürstenberger, Gerhard (FEBS letters, 1999)
A cDNA, recently cloned (by Krieg et al. (1998)) from mouse skin, was shown to encode a 12(R)-lipoxygenase. When expressed in HEK cells, the recombinant protein converted methyl arachidonate into the corresponding 12-HETE ester which was shown to be the R-enantiomer by chiral phase chromatography. Neither arachidonic acid nor linoleic acid were substrates for the recombinant protein. The structure of the 12(R)-lipoxygenase gene is unique among all animal lipoxygenases in that it is divided into 15 exons and 14 introns spanning approximately 12.5 kb. By interspecific backcross analysis, the 12(R)-lipoxygenase gene was localized to the central region of mouse chromosome 11.